Empowering Local Communities - Suteki, Suteki; Jalil, Abdul; Natalis, Aga; Nasution, Angelica Vanessa Audrey (Lentera Hukum, 2024)
When attaining effective governance and justice, as described in the Sustainable Development Goals (SDGs), corruption is a serious hurdle in sustainable development. The issue of corruption continues to be widespread in Indonesia, necessitating responses that are both comprehensive and international in scope. Essential to the fight against corruption is the empowerment of community engagement at the local level; in developing, implementing, and monitoring Anti-Corruption Action programs. On the other hand, there is considerable space for improvement regarding community participation in anti-corruption activities. This study aims to analyze the significance of community involvement in anti-corruption measures within Indonesia by employing a socio-legal methodology: a combination of legal research with sociological analysis. Data collection entails using primary sources, such as interviews and observations made in the field; in addition to secondary sources, including legal literature and decisions made by the courts. Descriptive-analytical approaches are used to examine the elements influencing community participation in preventing and eliminating corruption. After completing the research, the researchers concluded that anti-corruption learning programs, law enforcement, and community awareness are necessities to effectively combat corruption. Additionally notable is the increasing importance of the independent media's role in discovering corruption and increasing public awareness. Among the recommendations are the enhancement of community engagement, the promotion of anti-corruption education, the expansion of media cooperation, and the improvement of government openness. To combat corruption and promote good governance, it is possible to develop an effective and sustainable collaboration between the government and society by implementing these measures.KEYWORDS: Corruption, Community Engagement, Anti-Corruption Action Programs, Local Governance